2016
DOI: 10.1111/head.12776
|View full text |Cite
|
Sign up to set email alerts
|

Ergot Use and Overuse: A Pharmacoepidemiology Retrospective Cohort Study

Abstract: This work outlines a high prevalence of ergotamine tartrate overuse (11.1%). As ergotamine tartrate users are mostly aged more than 55 years, an evaluation of ergotamine cardiovascular risk profile is necessary in the elderly population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
4
1
Order By: Relevance
“…Another epidemiological study described the high prevalence of ergot users and overusers in an older population, but in our study we only found a low prevalence of ergot overusers (2.9%). A prospective study showed that triptan overusers outnumbered ergot overusers in the MOH population, hence triptan was the most common drug that caused MOH .…”
Section: Discussioncontrasting
confidence: 87%
“…Another epidemiological study described the high prevalence of ergot users and overusers in an older population, but in our study we only found a low prevalence of ergot overusers (2.9%). A prospective study showed that triptan overusers outnumbered ergot overusers in the MOH population, hence triptan was the most common drug that caused MOH .…”
Section: Discussioncontrasting
confidence: 87%
“…Amides and peptides containing lysergic acid have contaminated grain and forage crops resulting in human and animal toxicoses (1)(2)(3)(4). Additionally, derivatives of lysergic acid are used to synthesize a range of pharmaceuticals used to treat dementia, migraines, Parkinson's disease, and hyperprolactinemia (5)(6)(7)(8). Lysergic acidderived ergot alkaloids are produced by representatives of several genera in the fungal family Clavicipitaceae, including Claviceps spp., Epichloë spp., Balansia spp., and Periglandula spp.…”
mentioning
confidence: 99%
“…5Valvular heart disease can also be accompanied by myocardial ischemia, pain, claudication and ischemia in upper or lower limbs or a combination of the previous ones, and sometimes symptoms related to heart failure are the ones that lead the patient to consult. (6,7) This pathophysiological event is mediated by the stimulation of alpha adrenergic receptors in the smooth muscle, leading to an important vasospasm and loss of endothelial integrity; (8) some authors have tried to screen this population, Rasmussen VG, et al evaluated 138 patients who received treatment with ergotamine-derived agonists and described 25% of patients with some degree of valvular involvement, found severe aortic insufficiency (n = 4), moderate aortic insufficiency (n = 12), mitral (n = 3) and tricuspid valve insufficiency (n = 5). Two patients had a coexisting mitral insufficiency and moderate tricuspid valve insufficiency.…”
Section: Discussionmentioning
confidence: 99%